The Quest for Orthologs benchmark service and consensus calls in 2020. Issue Volume 48:Issue W1(2020) (6th May 2020) - Altenhoff, Adrian M; Garrayo-Ventas, Javier; Cosentino, Salvatore; Emms, David; Glover, Natasha M; Hernández-Plaza, Ana; Nevers, Yannis; Sundesha, Vicky; Szklarczyk, Damian; Fernández, José M; Codó, Laia; for Orthologs Consortium, the Quest; et al.
Abstract: The identification of orthologs—genes in different species which descended from the same gene in their last common ancestor—is a prerequisite for many analyses in comparative genomics and molecular evolution. Numerous algorithms and resources have been conceived to address this problem, but benchmarking and interpreting them is fraught with difficulties (need to compare them on a common input dataset, absence of ground truth, computational cost of calling orthologs). To address this, the Quest for Orthologs consortium maintains a reference set of proteomes and provides a web server for continuous orthology benchmarking (http://orthology.benchmarkservice.org ). Furthermore, consensus ortholog calls derived from public benchmark submissions are provided on the Alliance of Genome Resources website, the joint portal of NIH-funded model organism databases.